The survival of survival auditions: The effects of cultural memes in the Korean TV broadcasting industry - Doyoon Kim; Dongyoub Shin (PLoS ONE, 2025)
This study empirically analyzes the evolution of cultural products based on theoretical cultural discourse and evolutionary processes. We use data from 116 survival auditions aired in Korea between 2006 and 2017 to examine the cultural memes that shape the continued appeal of survival audition programs. Specifically, we discuss the influence of “memes” in cultural codes, namely, audience empowerment, experts’ involvement, fair rewards, and career opportunities. The results of probit regression analysis with survival audition program reproduction as the dependent variable show that audience empowerment, experts’ involvement, fair rewards, and career opportunities in survival audition programs influence the reproduction of cultural goods. The findings confirm all four hypotheses. The findings of this study have theoretical and practical implications. First, it enriches the theoretical discourse on the evolution of cultural goods by offering a meme-based explanation for their reproduction. Second, it has implications for industry practitioners involved in planning and producing cultural goods by identifying normative cultural codes that affect the longevity of these products.